Adsorption and Photocatalytic Properties of Immobilised Titanium Dioxide-Loaded Activated Carbon for Dye Removal - Chang, Sook Keng (2007)
With the development of industries and mushrooming of factories venturing into textiles, dyes, pigments, paints and so on, the condition and safety level of water bodies have worsened. Channeling these pollutants into the rivers may lead to unwanted and unsolved environmental problems. Therefore, various methods have been developed to overcome this escalating problem. Activated carbon adsorption is known as a remarkable process due to its large adsorption capacity without forming harmful intermediates or substances while photocatalytic degradation by TiO2 is a powerful process as it is capable of removing a wide range of organic compounds and achieving a complete mineralization of organics at the end of the process. Combining these two techniques will lead to the enhancement of the removal system. In this study, adsorption and photocatalytic degradation processes of Methylene Blue were conducted using immobilised mixture of titanium dioxide/activated carbon (TiO2/AC) under the illumination of ultraviolet (UV) lamp. Immobilised TiO2/AC was prepared by applying TiO2/AC onto a thin layer of PVA/formaldehyde binder that has been spread on glass. The physico-chemical properties of TiO2/AC were studied by Particle Size Analysis (PSA), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Accelerated Surface Area and Porosimetry Analysis (ASAP) and Infrared Analysis (IR). The removal process was studied by varying several parameters such as ball milling of AC in TiO2/AC, ratio of TiO2 and AC, suspension loading in the preparation of immobilised TiO2/AC, initial dye concentration, temperature and light source. The effects of UV light and supply of air towards the removal of cationic dyes: Methylene Blue (MB) and Victoria Blue R (VBR) and anionic dyes: Indigo Carmine (IC) and Naphthol Blue Black (NBB) using immobilised TiO2, AC and TiO2/AC were studied in terms of first-order and intraparticle diffusion models. Besides that, isotherm studies were done to determine the adsorption capacity of AC and TiO2/AC by testing 1000 ppm Methylene Blue using immobilised AC and TiO2/AC that varies in the number of glasses applied (1-5 glasses). Immobilised TiO2/AC showed its best performance under UV illumination with the usage of 1.5 g 30% TiO2/70% AC. Increasing the dye concentration leads to lower rate constant as the workload of the removal system has increased. The removal of Methylene Blue was an exothermic process. Besides that, immobilised samples containing AC was suitable for the removal of cationic dyes while anionic dyes were better removed by immobilised samples containing TiO2. The highest rate constants were obtained for these dyes under the illumination of UV light and air supply. The data also fitted well in intraparticle diffusion model. The adsorption capacity of AC and TiO2/AC was 370.37 mg/g and 344.83 mg/g respectively. The Langmuir equation gave a better fit to the adsorption isotherm than the Freundlich equation.